An infrageneric classification of Thesium (Santalaceae) based on molecular phylogenetic data. Issue 1 (11th April 2020) - Zhigila, Daniel A.; Verboom, G. Anthony; Muasya, A. Muthama
Abstract: Recent phylogenetic hypotheses reveal that Thesium (Santalaceae) is paraphyletic with respect to Austroamericium, Chrysothesium, Kunkeliella and Thesidium, suggesting the need for generic realignment. In addition, existing subgeneric and sectional classifications of this large genus lack a phylogenetic basis, thus compromising their predictive value. Using an expanded taxon sampling and a combination of nuclear (ITS) and chloroplast ( matK, rpl32‐trnL, trnL‐F ) DNA sequence data, we therefore re‐assessed the phylogenetic relationships of Thesium and used these as the basis of a new subgeneric classification of the genus. Our phylogeny confirms the need to sink the four segregate genera to render Thesium monophyletic. In addition, it resolves five well‐supported major clades within Thesium that we recognize as subgenera. Within Thesium, the South African endemic subgenus Hagnothesium is sister to the Eurasian subgenus Thesium (including Kunkeliella and Mauritanica ) . The subgenus Psilothesium, occurring in tropical South America (formerly genus Austroamericium ) and tropical Africa, is sister to the rest of the subgenera, which are all confined to South Africa. Within the latter, the subgenus Discothesium consists of subtropical and temperate species, whereas subgenus Frisea, comprising the previously recognized sections Annulata, Barbata, Frisea, Imberbia and Penicillata, is entirely of the Greater Cape Floristic Region. To facilitate identification of subgenera, we identify morphological ancestral characters and present an identification key, brief diagnoses, species assigned, distribution and ecological data .